2016
DOI: 10.1002/eco.1791
|View full text |Cite
|
Sign up to set email alerts
|

The potential for deep groundwater use by Acacia papyrocarpa (Western myall) in a water‐limited environment

Abstract: Knowledge regarding the use of groundwater by plants has implications for successful mine rehabilitation and revegetation programs in water‐limited environments. In this study, we combined several approaches to investigate water sources used by Acacia papyrocarpa (Western myall) in the far west of South Australia, including stable isotopes, water potential, groundwater and soil chemistry, and root mapping techniques. Plant δ18O signatures and water potentials were compared against a range of possible sources: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Measurements of plant water relations, such as water potential and stomatal conductance, can indicate if plants have access to sufficient water, and in combination with water isotope data can reveal where plants are obtaining their water (Eamus et al, 2006). Riparian trees often use groundwater (Busch et al, 1992; Snyder & Williams, 2000), however the proportion of groundwater used is variable, depending on the physiological attributes of species, such as root morphology, as well as environmental parameters such as seasonal water availability, soil type and position in the landscape (Lamontagne et al, 2005; Steggles et al, 2017). For example, in northern Australia there is evidence that riparian trees close to the river and at a lower elevation use more groundwater than riparian trees higher in the landscape (O'Grady, Cook, et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of plant water relations, such as water potential and stomatal conductance, can indicate if plants have access to sufficient water, and in combination with water isotope data can reveal where plants are obtaining their water (Eamus et al, 2006). Riparian trees often use groundwater (Busch et al, 1992; Snyder & Williams, 2000), however the proportion of groundwater used is variable, depending on the physiological attributes of species, such as root morphology, as well as environmental parameters such as seasonal water availability, soil type and position in the landscape (Lamontagne et al, 2005; Steggles et al, 2017). For example, in northern Australia there is evidence that riparian trees close to the river and at a lower elevation use more groundwater than riparian trees higher in the landscape (O'Grady, Cook, et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Deep soil moisture continues to be consumed with increasing forest age due to increased transpiration as the plants grow, but these plants tend to degrade when the initial water supply is depleted [ 33 , 34 ]. The results showed that the soil moisture at 200–400 cm decreased continuously after 11 years of growth, and it was difficult to maintain the rapid growth of Haloxylon ammodendron plantations with the shallow water added by precipitation after maturity.…”
Section: Discussionmentioning
confidence: 99%
“…Tree death due to prolonged wet conditions is well recorded in humid ecosystems (Assahira et al, 2017;Tzeng et al, 2018) and to that end extreme humidity can act as a stressor. Nevertheless our understanding of the use of surface vs. groundwater by deep rooted trees in more arid ecosystems is limited (Steggles et al, 2017).…”
Section: Discussionmentioning
confidence: 99%